2014
DOI: 10.1002/er.3221
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of representative power generation cycles for low-to-medium temperature applications

Abstract: SUMMARY This study is focused on the analysis of representative thermodynamic cycles for power generation at low‐to‐medium temperatures (with the highest cycle temperature from 450 to 700 K). The natural working fluid of carbon dioxide is selected for the current tests and comparisons with suitable operation ranges. Energy balance and exergy loss models are established and applied to 10 selected representative thermodynamic cycles. One modified efficiency parameter is also defined for better comparison of perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…15 Since the early 21st century, the research was revived and suggested by Dostal et al for application in the next generation reactor for high-temperature operations, as the S-CO 2 power cycle demonstrated higher efficiency than both the superheated steam Rankine cycle in TITs over 470°C and the supercritical steam over 550°C. 16,17 To further improve the cycle performance, the following investigations were conducted by the researchers: (a) comparing cycle layouts, such as the recompression cycle, the intercooling cycle, and the precompression cycle 10,18 ; (b) adopting the combined cycle and increase the bottom cycle, such as the Rankine cycle and the transcritical CO 2 cycle 19,20 ; (c) adding other gases to S-CO 2 to improve the physical properties of the working fluids 21 ; (d) reheating the working fluid to increase the turbine power. 10,22,23 Although some concept designs of the nuclear power generation systems utilized the S-CO 2 power cycle, [24][25][26] there are few studies on the coupling system of the pool-type liquid metal cooled fast reactor and the S-CO 2 cycle.…”
Section: Introductionmentioning
confidence: 99%
“…15 Since the early 21st century, the research was revived and suggested by Dostal et al for application in the next generation reactor for high-temperature operations, as the S-CO 2 power cycle demonstrated higher efficiency than both the superheated steam Rankine cycle in TITs over 470°C and the supercritical steam over 550°C. 16,17 To further improve the cycle performance, the following investigations were conducted by the researchers: (a) comparing cycle layouts, such as the recompression cycle, the intercooling cycle, and the precompression cycle 10,18 ; (b) adopting the combined cycle and increase the bottom cycle, such as the Rankine cycle and the transcritical CO 2 cycle 19,20 ; (c) adding other gases to S-CO 2 to improve the physical properties of the working fluids 21 ; (d) reheating the working fluid to increase the turbine power. 10,22,23 Although some concept designs of the nuclear power generation systems utilized the S-CO 2 power cycle, [24][25][26] there are few studies on the coupling system of the pool-type liquid metal cooled fast reactor and the S-CO 2 cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many modifications have been used, including an expander 16 and ejector, 17,18 thermoelectric subcooling 19 and mechanical subcooling, 20 multistage compression, 21,22 and internal heat exchanger. Therefore, many modifications have been used, including an expander 16 and ejector, 17,18 thermoelectric subcooling 19 and mechanical subcooling, 20 multistage compression, 21,22 and internal heat exchanger.…”
Section: Introductionmentioning
confidence: 99%
“…To improve energy efficiency of system and reduce operating pressure on the high-pressure side of the system, many experts have carried out theoretical and experimental research on different forms of the CO 2 transcritical single-stage cycle. Therefore, many modifications have been used, including an expander 16 and ejector, 17,18 thermoelectric subcooling 19 and mechanical subcooling, 20 multistage compression, 21,22 and internal heat exchanger. 23,24 Table 1 partially summarizes the previous research about transcritical CO 2 single-stage refrigeration cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, transcritical and supercritical CO 2 heat pump cycles [24,25] and power cycles [26,27] have been widely studied and developed. Moreover, CO 2 is one of the most promising natural working fluid because of its environment-benign nature and special properties of supercritical state.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CO 2 is one of the most promising natural working fluid because of its environment-benign nature and special properties of supercritical state. In the past few years, transcritical and supercritical CO 2 heat pump cycles [24,25] and power cycles [26,27] have been widely studied and developed.…”
Section: Introductionmentioning
confidence: 99%